2013
DOI: 10.5901/mjss.2013.v4n14p53
|View full text |Cite
|
Sign up to set email alerts
|

Drivers of E-Marketing Adoption among Small and Medium Enterprises (SMEs) and Variations with Age of Business Owners

Abstract: In a knowledge society, organisations need to develop competitive advantages through the effective utilization of electronic marketing in order to succeed in markets. The study complements existing literature and research by examining factors that assist in the adoption of electronic marketing by SMEs. Primary data was collected using a quantitative research technique through the use of a structured questionnaire. A random sample of 123 SMEs were drawn randomly within the various municipal areas in the Vaal Tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 61 publications
1
12
0
Order By: Relevance
“…In social media perspective, Sago (2013) examined factors impacting the adoption and frequency of use of various social media services such as Facebook, Twitter, Pinterest, and Google+ among undergraduate university students 18 to 23 years old, findings included the positive relationship between frequency of use of social media and its ease of use, enjoyment, and perceived usefulness. Dlodlo and Dhurup (2013) carried out a study on drivers of e-marketing adoption among small and medium enterprises (SMEs) and variations with age of business owners, a random sample of 123 SMEs were drawn randomly within the various municipal areas in the Vaal Triangle using principal component analysis with Varimax rotation five-dimensional structure, pertinent to the understanding of SMEs decisions to adopt e-marketing technology was established. Perceived ease of use (PEOU), external pressure, mission, job performance, resource availability and compatibility were found to be significant drivers of e-marketing adoption.…”
Section: Technological Context (Tc) and Adoption (Ad)mentioning
confidence: 99%
See 1 more Smart Citation
“…In social media perspective, Sago (2013) examined factors impacting the adoption and frequency of use of various social media services such as Facebook, Twitter, Pinterest, and Google+ among undergraduate university students 18 to 23 years old, findings included the positive relationship between frequency of use of social media and its ease of use, enjoyment, and perceived usefulness. Dlodlo and Dhurup (2013) carried out a study on drivers of e-marketing adoption among small and medium enterprises (SMEs) and variations with age of business owners, a random sample of 123 SMEs were drawn randomly within the various municipal areas in the Vaal Triangle using principal component analysis with Varimax rotation five-dimensional structure, pertinent to the understanding of SMEs decisions to adopt e-marketing technology was established. Perceived ease of use (PEOU), external pressure, mission, job performance, resource availability and compatibility were found to be significant drivers of e-marketing adoption.…”
Section: Technological Context (Tc) and Adoption (Ad)mentioning
confidence: 99%
“…It personalizes the brand and helps companies to spread their message in an often relaxed and conversational way (ibid).On the related perspective, Brad (2013) advocate that, social networking media as an extension of the world wide web, it has expanded the opportunities for small businesses to compete with larger, global companies. In a knowledge society like tourism, Dlodlo and Dhurup (2013) argued that organizations need to develop competitive advantages through the effective utilization of electronic marketing in order to succeed in the markets. The adoption and use of Information and Communications Technologies (ICT), in particular social media, has the potential to strengthen SMEs in tourism, by providing them tools to meet the needs of the domestic market online, enable access to an increasingly global market place and leverage SMEs as a destination for foreign investment.…”
Section: Introductionmentioning
confidence: 99%
“…Various studies have identified factors considered to be prerequisites for adopting and deploying e-Marketing innovation in an organization. The impact of e-Marketing on firm's performance and profitability in developed and developing countries have led to a lot of research in the literature on the influences of its adoption by firms (Dlodlo and Dhurup, 2013). Notably, firms would only adopt and deploy technologies that are in harmony to their line of business and such technologies would have to offer relative benefits (Rashid and Al-Qirim, 2001).…”
Section: Empirical Literatures Of the Studymentioning
confidence: 99%
“…The scale used for innovation was proposed by Pinzón (2009), which considers four dimensions: product innovation; processes innovation; marketing innovation; and organization innovation with a total of 27 items. The scale used for digital marketing was developed by Dlodlo & Dhurup (2013), which include five dimensions: perceived ease of use; external pressure and goal; job performance; availability of resources; and compatibility with a total of 13 items. Both measurements scales are based on a Likert-type scale of five positions from "1 = completely disagree to 5 = completely agree" as limits.…”
Section: Methodsmentioning
confidence: 99%